2006
DOI: 10.1111/j.1440-1746.2005.04219.x
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic characteristics and Helicobacter pylori infection in NSAID‐associated gastric ulcer

Abstract: In contrast to non-NSAID-associated gastric ulcers, NSAID-associated gastric ulcers frequently occur in the antrum with bleeding. The rate of H. pylori infection in NSAID-associated gastric ulcers is significantly lower than that in non-NSAID-associated gastric ulcers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…Currently, it is not known whether the differential impact of COX inhibitors on OATP2A1 function may contribute to the gastrointestinal side effects of COX inhibitors. NSAID-induced gastroduodenal complications are most frequent in the antrum, followed by the corpus (Kamada et al, 2006), and our results indicate that OATP2A1 expression levels follow the same order. It is known that the blockade of cyclooxygenases by COX inhibitors is a major cause for NSAID-induced gastrointestinal ulcerations.…”
Section: Downloaded Fromsupporting
confidence: 58%
“…Currently, it is not known whether the differential impact of COX inhibitors on OATP2A1 function may contribute to the gastrointestinal side effects of COX inhibitors. NSAID-induced gastroduodenal complications are most frequent in the antrum, followed by the corpus (Kamada et al, 2006), and our results indicate that OATP2A1 expression levels follow the same order. It is known that the blockade of cyclooxygenases by COX inhibitors is a major cause for NSAID-induced gastrointestinal ulcerations.…”
Section: Downloaded Fromsupporting
confidence: 58%
“…In consideration of the mean age of patients (68.2± 8.3 years), we had an impression that the positivity rate was low. According to a recent study (9), the H. pylori infection rate in patients with non-NSAID-induced ulcer whom we encounter in routine medical practice is !90% in contrast to a rate of 50% in patients with NSAID-induced ulcer. NSAID-induced ulcer is considered to develop preferentially in patients without H. pylori infection.…”
Section: Discussionmentioning
confidence: 99%
“…An Italian study of symptomatic elderly chronic users of low-dose aspirin found that the prevalence of peptic ulcers was significantly higher (36.6% versus 15.8%) among H. pylori-positive subjects than the H. pylori-negative subjects (17). However, in another study in Japan, the prevalence of (H. pylori) infection was found to be significantly lower in patients considered to have NSAID-associated gastric ulcer than in age-matched non-NSAID-associated gastric ulcer patients (48% versus 96%) (18). Our findings possibly reflect the differences in the prevalence or severity of H. pylori gastritis between different countries.…”
Section: Discussionmentioning
confidence: 80%